Investigating Criminal Responsibility of International Organizations in the International Law System - Abbas Rafiee (International Journal of Ethics and Society, 2021)
Background: In addition to governments, the activities of international organizations such as a large multinational corporation may be detrimental and hazardous to international public order. For example, companies that produce microbial and chemical bombs and organizations that traffic women, children, opiates in addition to buying and selling human organs, or that carry out sexual terrorism and international prostitution. The objective of the present study is on the criminal responsibility of international organizations in the international law system as well as whether international law has ever attempted to identify the criminal responsibility of such persons?